2010
DOI: 10.2116/analsci.26.467
|View full text |Cite
|
Sign up to set email alerts
|

Stability indicating HPTLC method for determination of terbutaline Sulfate in bulk and from Submicronized dry Powder inhalers

Abstract: A stability-indicating high-performance thin-layer chromatographic (HPTLC) method has been developed for the determination of terbutaline sulfate (TBS) as a bulk drug and in pharmaceutical formulations (submicronized dry powder inhalers). The separation was achieved on TLC aluminum plates precoated with silica gel 60F-254 using chloroform-methanol (9.0:1.0 v/v) as mobile phase. The densitometric analysis was carried out at 366 nm wavelength. Compact spots appeared at Rf = 0.34 ± 0.02. For the proposed procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…[13] In brief, samples were spotted in the form of bands of width 6 mm with a Camag microlitre syringe on precoated silica gel aluminum Plate 60 F–254 (20 × 10 cm with 250 μm thickness; E. Merck, Darmstadt, Germany, supplied by Anchrom Technologists, Mumbai, India) using a Camag Linomat IV (Muttenz, Switzerland). The plates were prewashed by methanol and activated at 60°C for 5 min prior to chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…[13] In brief, samples were spotted in the form of bands of width 6 mm with a Camag microlitre syringe on precoated silica gel aluminum Plate 60 F–254 (20 × 10 cm with 250 μm thickness; E. Merck, Darmstadt, Germany, supplied by Anchrom Technologists, Mumbai, India) using a Camag Linomat IV (Muttenz, Switzerland). The plates were prewashed by methanol and activated at 60°C for 5 min prior to chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…There are some other literature review showed the estimation of these drug in combination with another drug formulation by different analytical methods such as, spectrophotometric simultaneous analysis of Ambroxol Hydrochloride, Guaifenesin and Terbutaline Sulphate in liquid dosage form such as syrup 25 , RP-HPLC and stability indicating HPLC methods for simultaneous determination of Terbutaline alone and with combinations [26][27][28][29] , simultaneous determination of Terbutaline Sulphate with other drugs in tablet formulation by UV Spectrophotometry 30 , stability indicating HPTLC method for determination of Terbutaline Sulphate in bulk and from submicronised dry powder inhalers 31 . Thus, this present study report deals with the simultaneous estimation of Doxofylline and Terbutaline Sulphate by HPLC in bulk drug and tablet dosage form.…”
Section: Fig 2: Structure Of Doxofyllinementioning
confidence: 99%
“…A validated HPLC method for the determination of TB and its possible degradation products has been reported in literature [16], utilizing Hypersil 100 C 18 , 150 4.6 mm (5 m) column, found inadequate sensitivity of the method due to high limit of quantitation (LOQ; 0.11 g mL -1 ) and limit of detection (LOD; 0.37 g mL -1 ) values. In our previous study, a stability-indicating high performancethin layer chromatography (HPTLC) has been developed and validated for the direct estimation of TB and its potential degradants in bulk and submicronized dry powder inhalers *Address correspondence to this author at the Department of Pharmaceutics, Faculty of Pharmacy, Hamdard University, New Delhi-110062, India; Tel: +91-7668963486; E-mail: md.faiyazuddin2008@gmail.com [17]. The low value of LOQ (28.35 ng spot -1 ) and LOD (9.41 ng spot -1 ) indicated adequate assay sensitivity of our reported method.…”
Section: Terbutaline (Tb) An Amphiphilicmentioning
confidence: 99%